The Influence Of Online Customer Reviews, Trust And Ratings On Purchasing Interest In The Tokopedia Marketplace On UNPRI Faculty Of Psychology Students - Events, Events; Jarungjung Hutagaol; Nirwana Br Bangun (SEAN Institute, 2024)
This research aims to determine and analyze the influence of Customer Online Reviews, Trust and Ratings on Purchase Interest at the Tokopedia Marketplace among UNPRI Faculty of Psychology Students. Negative reviews of services and products from online stores, lack of customer trust in online stores and low ratings cause a decrease in requests for purchases from customers. The theories used in this research are Marketing Management theories, which relate to Customer Online Reviews, Trust, Ratings and Purchase Intentions. Explanatory descriptive is the nature of this research, quantitative descriptive is the research method utilized, and quantitative approach is the research type. Through the use of questionnaires, documentation studies, and interviews, data was collected. Multiple regression analysis serves as the analytical technique. The population used was all 106 students from the Faculty of Psychology in the 2021-2023 academic year. Determination of the sample in this study used saturated sampling. The results of the research show that Customer Online Reviews, Trust and Ratings have a significant effect on Purchase Interest at the Tokopedia Marketplace among UNPRI Faculty of Psychology Students. The trust variable is the one that has the most effect on purchase interest out of the three variables examined, according to the examination of the factors influencing purchase interest. The t count findings for each variable demonstrate this.